New trends of the civil justice in Hungary - Viktória Harsági (Bratislava Law Review, 2019)
The article provides an overview on the most important innovations of the new Hungarian Code of Civil Procedure. It presents a renewed system of allocation of cases, the split structure of the procedural phases, the modifications in connection of the representation, the new regulation on the illegaly obtained evidence, the solutions for incapacity to prove, the remedies and collective redress. Finally, the manuscript goes on with the question of electronization and try to evaluate the modest practical experience of these innovations so far.